Flinovia - Flow Induced Noise and Vibration Issues and Aspects: A Focus on Measurement, Modeling, Simulation and Reproduction of the Flow Excitation and Flow Induced Response - Ciappi, E (Springer, 2016)
Flow induced vibration and noise (FIVN) remains a critical research topic. Even after over 50 years of intensive research, accurate and cost-effective FIVN simulation and measurement techniques remain elusive. This book gathers the latest research from some of the most prominent experts in the field.